Teotihuacán, [v. 1], pte. 2 : el caracol alado - Gómez Sáenz, Pablo; Infante, Gonzálo; Braojos, Ricardo; Rocha, Claudio (México : Consejo Nacional para la Cultura y las Artes, 1992)
Muestra las obras arquitectónicas construidas por los indios en Teotihuacán (México).
Keywords: INDIOS MEXICANOS -- ARQUITECTURA; TEOTIHUACAN (MEXICO) -- ANTIGUEDADES